Gensko zdravljenje avtoimunskih bolezni - Mlinar, Eva (Placebo, 2022)
very promising, especially in the field of difficult-to-cure autoimmune diseases, genetic diseases and various types of cancer. It works on the principle of modifying the genetic material by replacing or inhibiting certain genes. This can be achieved by inserting genes into somatic or germ cells, in in vivo or ex vivo conditions. Positive results can already be observed in many clinical trials when treating autoimmune diseases such as multiple sclerosis and rheumatoid arthritis. Despite the positive results, gene therapy is in the early stages of research, where concerns about the safety of the therapy itself remain, due to its possible side effects such as tumor formation and adverse immune responses.
Keywords: autoimmune disease; Avtoimunske bolezni; gene therapy; gensko zdravljenje; germ cells; Multipla skleroza; multiple sclerosis; Revmatoidni artritis; rheumatoid arthritis; somatic cells; somatske celice; zarodne celice